2013
DOI: 10.1111/nph.12402
|View full text |Cite
|
Sign up to set email alerts
|

On the cellular site of two‐pore channel TPC1 action in the Poaceae

Abstract: SummaryThe slow vacuolar (SV) channel has been characterized in different dicots by patch-clamp recordings. This channel represents the major cation conductance of the largest organelle in most plant cells. Studies with the tpc1-2 mutant of the model dicot plant Arabidopsis thaliana identified the SV channel as the product of the TPC1 gene. By contrast, research on rice and wheat TPC1 suggested that the monocot gene encodes a plasma membrane calcium-permeable channel.To explore the site of action of grass TPC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 70 publications
(160 reference statements)
2
14
0
Order By: Relevance
“…2. 'Two-pore cation channel' (TPC) The two-pore channel 1 (TPC1) has a single gene in A. thaliana (Peiter et al, 2005), functioning as a dimer and encoding the conductance of the socalled 'slow vacuolar' (SV) channel, which has been electrophysiologically characterized in detail (Hedrich & Marten, 2011;Pottosin & Dobrovinskaya, 2017). This homologous channel exists in plants, animals and protists (Hedrich & Marten, 2011;Dadacz-Narloch et al, 2013;Patel & Cai, 2015). TPC1 channels dominate vacuolar Ca 2+ conductance (Pottosin et al, 2009) and its relative expression determines the vacuolar Ca 2+ storage capacity .…”
Section: New Phytologistmentioning
confidence: 99%
“…2. 'Two-pore cation channel' (TPC) The two-pore channel 1 (TPC1) has a single gene in A. thaliana (Peiter et al, 2005), functioning as a dimer and encoding the conductance of the socalled 'slow vacuolar' (SV) channel, which has been electrophysiologically characterized in detail (Hedrich & Marten, 2011;Pottosin & Dobrovinskaya, 2017). This homologous channel exists in plants, animals and protists (Hedrich & Marten, 2011;Dadacz-Narloch et al, 2013;Patel & Cai, 2015). TPC1 channels dominate vacuolar Ca 2+ conductance (Pottosin et al, 2009) and its relative expression determines the vacuolar Ca 2+ storage capacity .…”
Section: New Phytologistmentioning
confidence: 99%
“…TPC1 is found in all land plants (14) and the function of this channel appears to be conserved at least between monocots to dicots (27). This ubiquity of TPC1 suggests a possibly widespread and general function of this channel in plant biology, hinting at the potentially widespread nature of Ca 2+ wave signaling in plants.…”
Section: Role Of the Vacuolar Ion Channel Tpc1 In Propagation Of The mentioning
confidence: 99%
“…One dispute concerning TPC1 localization was recently resolved, when it was shown that an N‐terminal motif directs Arabidopsis TPC1 to tonoplast (Larisch et al ., ). While the rice TPC1 was reported to be in plasma membranes (Hamada et al ., ), recent evidence points to lysovacuolar localization for TPC1 from both monocot and dicot plants (Dadacz‐Narloch et al ., ), and even animal TPCs (Cang et al ., ). If TPC1 is indeed the main tonoplast Ca 2+ channel, it remains unclear why loss of the singleton AtTPC1 gene did not reveal any obvious Ca 2+ ‐regulated phenotypes in a wide range of stress scenarios (Ranf et al ., ).…”
Section: Nature Of Plant Ca2+ Channels and Pumpsmentioning
confidence: 99%